Building Harmony in Diversity: A Study of Pluralism and Multiculturalism in Indonesia - Saepulmilah, Ceceng; Musthafa, Luqman Al-Hakim; Ruswandi, Uus (SAINTIS Publishing, 2025)
This research aims to analyze the concepts of pluralism and multiculturalism as well as the challenges and opportunities for their implementation in building social harmony in Indonesia through an educational approach. Using the literature study method and content analysis technique, this research examines various scientific sources related to pluralism, multiculturalism, and educational practices in plural societies. The analysis shows that pluralism and multiculturalism have a strategic position in building an inclusive and democratic society. However, the implementation of these values still faces various challenges such as cultural exclusivism, politicization of identity, and limited curriculum and teacher competence in multicultural education. On the other hand, there is great potential in implementing strategies such as strengthening diversity-based curriculum, integrating local wisdom values, and adaptive and contextual social education innovations. The research also highlights the importance of intercultural and interreligious dialogue, as well as collaboration between the government, educational institutions and communities in shaping a tolerant and just social environment. The conclusion of this research confirms that diversity management requires a comprehensive, systemic approach, rooted in local values, in order to create sustainable social harmony within the framework of the Indonesian nation state.